Thermal extremes can intensify chemical toxicity to freshwater organisms and hence exacerbate their impact to the biological community. (June 2019) - Wang, Zhen; Lui, Gilbert C.S.; Burton, G.Allen; Leung, Kenneth M.Y.
Abstract: Temperature in freshwater ecosystems fluctuates daily, seasonally and yearly. Climate change further induces temperature variations. In this study, we hypothesise that water temperatures, in particular thermal extremes, can significantly influence chemical toxicity to ectothermic organisms. Although temperature-dependent chemical toxicity (TDCT) is a classic research area in ecotoxicology, a unified model for predicting TDCT for freshwater species is yet to be developed. This study aimed to address this challenging issue through a meta-analysis by comparing acute toxicity endpoints (i.e. median lethal or effective concentration data; LC50 or EC50 ) of 13 chemicals for various freshwater species generated from different temperatures. Our results suggest that in most cases, freshwater species exhibit the highest tolerance towards chemicals at their physical optimal temperature ( T opt ), and chemical toxicity exacerbates when temperature is higher or lower than T opt (i.e. inverted V-shaped model between temperature and LC50 or EC50 ). Such observations are further supported by temperature-dependent hazardous concentration 10% (HC10 ) values derived from species sensitivity distributions constructed using toxicity data generated at different temperatures. A unified mathematical model was also developed to describe the inverted V-shape relationship between temperature and HC10 derivations. Overall, considering the natural variations of freshwater temperatures, the inverted V-shaped TDCT model can be readily applied to derive water quality guidelines and assess ecological risks of chemical contaminants. Graphical abstract: Image 1 Highlights: Freshwater species mainly follow negative linear and inverted-V shaped TDCT models. The inverted-V shaped model can better describe temperature–toxicity relationship. The inverted-V shaped relationship was characterised by temperature-dependent HC10 s. A mathematical model was developed to validate the inverted-V shaped model.